Targeted Knockdown of Overexpressed VEGFA or VEGF164 in Müller cells maintains retinal function by triggering different signaling mechanisms - Becker, Silke; Wang, Haibo; Simmons, Aaron B.; Suwanmanee, Thipparat; Stoddard, Gregory J.; Kafri, Tal; Hartnett, M. Elizabeth (Scientific reports, 2018)
Oxygen-induced retinopathy (OIR) upregulates Müller cell vascular endothelial growth factor A (VEGFA) that causes intravitreal neovascularization similar to severe retinopathy of prematurity (ROP). Safety concerns exist with anti-VEGF treatment for ROP. We evaluated long-term knockdown of Müller cell-VEGFA with short-hairpin RNAs to VEGFA or VEGF 164 via subretinal lentivirus delivery (L-VEGFAshRNA, L-VEGF164shRNA) on retinal structure and function in a rat OIR model. Lectin-stained retinal flat mounts analyzed for areas of avascular/total retina (AVA) and intravitreal neovascular/total retina (IVNV) showed initial significantly reduced IVNV by L-VEGFAshRNA and L-VEGF164shRNA compared to control, luciferase-shRNA lentivirus, without late recurrence. Spectral-domain optical coherence tomography (OCT) and immunohistochemical sections (IHC) demonstrated changes in retinal layer thicknesses in L-VEGFAshRNA or L-VEGF164shRNA  compared to control. Ganzfeld electroretinograms were increased in L-VEGFAshRNA or L-VEGF164shRNA compared to control. Erythropoietin (EPO), brain-derived neurotrophic factor, glial-derived neurotrophic factor, nerve growth factor, neurotrophin-3 (NT-3) mRNAs were increased in L-VEGFAshRNA, but not L-VEGF164shRNA retinas. In cultured rat Müller cells, knockdown of VEGF upregulated NT-3 and EPO, whereas treatment with EPO activated neuroprotective signaling. Methods to reduce IVNV by selective knockdown of VEGFA, and particularly VEGF 164 , in Müller cells may have fewer deleterious effects than nonselective VEGFA inhibition to all cells in the retina.